Climatic implications of the Quaternary fluvial tufa record in the NE Iberian Peninsula over the last 500 ka. Issue 3 (November 2015) - Sancho, Carlos; Arenas, Concha; Vázquez-Urbez, Marta; Pardo, Gonzalo; Lozano, María Victoria; Peña-Monné, José Luis; Hellstrom, John; Ortiz, José Eugenio; Osácar, María Cinta; Auqué, Luis; Torres, Trinidad
Abstract : The drainage area of the Iberian Ranges (NE Spain) houses one of the most extensive Quaternary fluvial tufaceous records in Europe. In this study, tufa deposits in the Añamaza, Mesa, Piedra and Ebrón river valleys were mapped, stratigraphically described and chronologically referenced from U/Th disequilibrium series, amino acid racemization and radiocarbon methods. Tufa deposits accumulated in cascades, barrage-cascades and related damming areas developed in stepped fluvial systems. The maximum frequency of tufa deposition was identified at 120 ka (Marine Oxygen Isotope Stage [MIS] 5e), 102 ka (MIS 5c), 85 ka (~ MIS 5a) and 7 ka (MIS 1), probably under warmer and wetter conditions than today. Additional phases of tufa deposition appear at ~ 353 ka (~ end of MIS 11), 258–180 ka (MIS 7) and 171–154 ka (MIS 6). Although most tufa deposition episodes are clearly correlated with interstadial periods, the occurrence of tufa deposits during the penultimate glaciation (MIS 6) is remarkable, indicating that the onset of this stage was climatically favourable in the Iberian Peninsula. Biostatic conditions and the dynamics of karstic systems regulating tufa deposition seem to be sensitive to the precipitation regime, controlled by shifts in the position of North Atlantic atmospheric belts, and summer insolation, regulated by orbital forcing.